Coexistence between Nearctic-Neotropical migratory shorebirds and humans on urban beaches of the Southern Hemisphere: a current conservation challenge in developing countries - Cestari, Cesar (UNESP) (Springer, 2015)
The arrival of migratory shorebirds on beaches in urban communities in developing countries is a current challenge for the protection of these migrant birds. Nearctic-Neotropical migrants rely on roosting and feeding sites during their stopover on wintering sites in the Southern Hemisphere to acquire sufficient energy to complete their migratory cycles. On the other hand, cities in the Southern Hemisphere are growing rapidly, which results in increasing competition for space between humans and birds, such as for use in beach habitats. In the present study, I analyze the probability for occurrence for Nearctic-Neotropical migratory birds relative to the number of people in southeastern Brazil, the most populated region of South America. The frequency of occurrence of migrants, their distance of tolerance to people and the number of people were recorded in sample areas (circle plots with 20 m radius) on a 9 km stretch of urban beaches from November to February from 2009 to 2013. The probability of occurrence of Nearctic birds decreased as the number of people increased. When the number of people exceeded 20, the probability of occurrence of birds was almost zero. Furthermore, more than 95 % of birds moved off when people were within 16 m of reach. These results are discussed in the context of conservation actions since no management plan has been developed for migrant shorebirds that use urban beaches as stopover or wintering sites in developing countries.
Keywords: Adaptive management; Charadriidae; Conservation; Migration; Scolopacidae; South America